PENINGKATAN EFISIENSI PRODUKTIVITAS UMKM KERIPIK TEMPE SAGU “BULANKOE” CILEUNGSI KABUPATEN BOGOR - Perak Samosir (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2022)
The impact of the COVID-19 pandemic in 2020 will be increasingly felt by small industrial business actors in 2021. One of them is the Center for Research and Community Service of the Indonesian Institute of Technology (PRPM ITI), namely the UMKM Tempe Sago Chips